Transparent cloud storage aggregator - Aung, Aye Phyu Phyu (2015)
Nowadays, there is a vast increase in the number of people who use online cloud services such as Google Drive and Dropbox as their primary and portable data storage for files and data. Due to the limitations of these services with respect to free storage, the popular features of these storage services (for example, sharing and transferring) become inconvenient and difficult for most users. Thus, the objective of this project, Transparent Cloud Storage Aggregator (TCSA), is to build a transparent and platform-independent application, which aggregates two supported cloud services, namely Google Drive and Dropbox, providing a unified service with a much larger storage. In addition to this, the application includes the encryption module built into the client side browser for improved data security. The TCSA was developed as a browser extension in JavaScript. All of these happen seamlessly in the background without the need of monitoring by the client. Moreover, sharing encrypted files among the users could be catered as an extension of the project. Erasure coding to enhance the security of encryption is also discussed for further development.